Cultivation and Propagation Techniques of Trichoderma harzianum - Aluna Gita Arumsari; Alfidhiya Amany Ramli; Neil Priharto; Sunardi Ikay; Risa Rosita (SEAMEO BIOTROP, 2023)
This research was conducted to determine the effect of temperature on the growth of Trichoderma harzianum. Trichoderma harzianum has functions to prevent the growth of diseases in plants, increase plant growth, and decompose organic matter. The research was conducted at the Phytopathology and Biosystem and Landscape Management Laboratory at SEAMEO BIOTROP, Bogor. The study was analyzed using a Completely Randomized Design (CRD) with different temperature treatments with five replications. The parameter observed was the diameter of the fungus growth after 6 days incubation period. Based on the research results, T. harzianum grew well when the fungus was incubated at 23 °C compared to 40 °C.